Antinuclear, anti-dsDNA and anti-ENA antibodies in patients affected with rheumatoid arthritis or ankylosing spondylitis during treatement with infliximab - L. Punzi; U. Fiocco; C. Botsios; M. Podswiadek; P. Grypiotis; A. Ruffatti; A. Hoxha; S. Todesco (PAGEPress Publications, 2011)
Objective: We evaluated the induction and clinical significance of ANA, anti-dsDNA and anti-ENA during infliximab therapy in patients with Rheumatoid Arthritis (RA) or Ankylosing Spondylitis (AS). Methods: We tested sera from 30 RA and 30 AS patients before and during treatment with infliximab. ANA and antidsDNA were determined by indirect immunofluorescence and anti-ENA by an "in house" counterimmunoelectrophoresis. Statistical analysis was performed by X2 and McNemar's tests and U-test of Mann-Whitney. Results: Eight of the 30 RA patients and 1 of the 30 AS patients were positive for ANA before treatment with infliximab. Eighteen of the 22 (81.8%) negative patients with RA and 11 of the 29 (37.9%) negative patients with AS became positive for ANA during infliximab treatment. No ANA positive patients became negative during the therapy. The difference between ANA before and after treatment resulted significant in both RA and AS patients (p=0.001). The frequency of anti-dsDNA and anti-ENA did not change significantly from baseline, in both RA and AS patients. Acquired ANA positivity was not associated with clinical signs of lupus syndrome and was not correlated with adverse events. The mean values of ESR and CRP in RA patients who became positive for ANA were significantly decreased (p=0.01 and p=0.02 respectively). Conclusions: Infliximab treatment induced a significant increase in the frequency of ANA in RA and AS patients. The significance of ANA development in these diseases is at present unknown. The significant decrease of ESR and CRP in RA patients who became positive for ANA after treatment should be investigated in a larger number of patients.